Revisiting Bronze and Early Iron Age Central Epirus (Prefecture of Ioannina, Greece) - Vasileiou, Eleni (Journal of Greek Archaeology, 2018)
The area of central Epirus (prefecture of Ioannina) occupies the northwestern part of the Greek peninsula. It has been continuously settled for a quarter of a million years during which it witnessed lots of changes of physical landscape owing mainly to the intense tectonic activity. Central Epirus is dominated by two different geographical units, the Ioannina basin and the mountains surrounding it (Figure 1).